2014
DOI: 10.15376/biores.9.4.6627-6643
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Atrazine in Tropical Soil by Biochar Prepared from Cassava Waste

Abstract: Biochar (BC) is a carbonaceous and porous product generated from the incomplete combustion of biomass and has been recognized as an efficient adsorbent. This study evaluated the ability of BC to sorb atrazine pesticide in tropical soil, and explored potential environmental values of BC on mitigating organic micro-pollutants. BC was produced from cassava waste via pyrolyzation under oxygen-limiting conditions at 350, 550, and 750 °C (MS350, MS550, and MS750, respectively). Three biochars were characterized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Post-processing handling also influenced herbicide sorption. Clay and Malo [13] and Deng et al [49] also reported atrazine sorption differed among different processing types within a feedstock species. Higher heat, longer processing times, and particle size have been reported to influence sorption.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Post-processing handling also influenced herbicide sorption. Clay and Malo [13] and Deng et al [49] also reported atrazine sorption differed among different processing types within a feedstock species. Higher heat, longer processing times, and particle size have been reported to influence sorption.…”
Section: Discussionmentioning
confidence: 96%
“…[39] Increased atrazine sorption to biochar amended soil has been reported in many studies. [13,30,49] Other studies have shown higher sorption of neutral herbicides (treflan and pendimethalin). [32,51] Acidic herbicides, like 2,4-D, are less sorbed to soil when compared with slightly positively charged herbicides like atrazine, but sorption also is influenced by soil organic matter content and pH.…”
Section: Discussionmentioning
confidence: 97%
“…Several weak peaks were observed in the region of 850 to 620 cm -1 and were determined to be the C-H bending for aromatic out-of-plane deformation. Nevertheless, the disappearance of some distinctive peaks with increased pyrolysis temperature, such as O-H (3400 cm -1 ), C-H (2920 and 2875 cm -1 ), and C=O (1650 cm -1 ) vibrations, suggested there was a breakdown of cellulose and lignin, as well as the removal of hydrogen and oxygen in the carbonization process (Deng et al 2014). It was noted that the peaks at 3400 cm -1 (O-H) and 1060 cm -1 (C-O) were slightly shifted to 3450 cm -1 and 1045 cm -1 , respectively, after the sorption of OTC, which indicated the involvement of hydrogen bonding interaction during OTC adsorption (Wahab et al 2010).…”
Section: Ftir Analysismentioning
confidence: 99%
“…Biochar is an excellent sorbent due to its large specific surface area, abundant microporous structure, high hydrophobicity, and aromaticity (Jonker et al 2004). Biochar could effectively remove various pollutants, such as heavy metals, polycyclic aromatic hydrocarbons (PAHs), steroid hormones, pesticides, and antibiotics (James et al 2005;Sarmah et al 2010;Deng et al 2014;Mohan et al 2014;Feng et al 2015). Thus, biochar can potentially be used as an effective and inexpensive sorbent for adsorbing contaminants from environment.…”
Section: Introductionmentioning
confidence: 99%
“…pine wood and dairy waste manure) have been frequently used for atrazine removal which is significantly affected by soil DOC and pH. For example, at low pH values (pH < 3), cassava waste biochar prepared at -750 °C and applied at 1% sorbed up to 86.6% of atrazine in an artificially contaminated krasnozem soil (20 mg L -1 ) (Deng et al 2014). In a related study, southern crabgrass, common lambsquarter, lettuce and wheat biochars were effective in removing atrazine by 89, 34, 100, and 45%, respectively although its herbicidal activity was also greatly reduced (Soni et al 2015).…”
Section: Atrazine (2-chloro 4-ethylamino 6-isopropylamino-s-triazine)mentioning
confidence: 99%